2016
DOI: 10.3389/fpls.2016.00690
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Medium-Chain Fatty Acid Synthesis in Synechococcus sp. PCC 7002 by Replacing FabH with a Chaetoceros Ketoacyl-ACP Synthase

Abstract: The isolation or engineering of algal cells synthesizing high levels of medium-chain fatty acids (MCFAs) is attractive to mitigate the high clouding point of longer chain fatty acids in algal based biodiesel. To develop a more informed understanding of MCFA synthesis in photosynthetic microorganisms, we isolated several algae from Great Salt Lake and screened this collection for MCFA accumulation to identify strains naturally accumulating high levels of MCFA. A diatom, Chaetoceros sp. GSL56, accumulated partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…In Ss7002, Kuo and Khosla determined that FabH was the rate-limiting enzyme of FAS using in vitro reconstituted systems and suggested that, either overexpressing the endogenous fabH gene or by replacement with its E. coli ortholog, the FA flux should be increased [ 17 ]. Attempts to delete fabH in Ss7002 proved impossible, rendering always non-pure deficient mutants and thus suggesting that fabH is essential in this cyanobacterium [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ss7002, Kuo and Khosla determined that FabH was the rate-limiting enzyme of FAS using in vitro reconstituted systems and suggested that, either overexpressing the endogenous fabH gene or by replacement with its E. coli ortholog, the FA flux should be increased [ 17 ]. Attempts to delete fabH in Ss7002 proved impossible, rendering always non-pure deficient mutants and thus suggesting that fabH is essential in this cyanobacterium [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Se7942, the fabH deletion was lethal, when assayed by random barcode transposon site sequencing (RB-TnSeq) [ 29 ]. Neither was this gene removed from all chromosomal copies of Ss7002 [ 27 ]. Our attempts to delete fabH in Se7942 also resulted in merodiploid mutants, an indication of the indispensability of this gene, and that no other Se7942 KAS enzyme (e.g., FabF) can act as a functional replacement for FabH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GSL56 helped to identify putative enzymes of the FA synthesis pathway. In addition, replacement of ketoacyl-ACP synthase of Synechococcus 7002 with Chaetoceros ketoacyl-ACP synthase III induced FA synthesis [17]. In line with this, TAG accumulating conditions increased the levels of transcripts for KAS in H. pluvialis [15].…”
Section: As Shown Inmentioning
confidence: 56%
“…It is noteworthy that these short or medium chain length specific thioesterases should be expressed in the aas mutant to avoid the reactivation and the elongation of FFAs (Table 1). In addition, the replacement of the native FabH with a Chaetoceros ketoacyl-ACP synthase III in the lauric acid-secreting strain of Syn7002 increased MCFA synthesis up to five-fold (Gu et al, 2016).…”
Section: Heterologous Metabolic Pathway Engineering Toward Ffas and Cmentioning
confidence: 99%